Optimization of oxy-fuel circulating fluidized bed combustion system with high oxygen concentration - Runjuan Kong (Elsevier, 2022)
High oxygen concentration oxy-fuel circulating fluidized bed (CFB) combustion technology is a high efficiency and low cost oxy-fuel combustion technology, which also has high potential of optimization and efficiency improvement. In this research, energy efficiency is analysed to acquire the effects of flue gas recirculation mode, preheating temperature and oxygen purity on the net efficiency and energy consumption of the 50% oxy-fuel combustion system, so as to obtain the further optimization strategy. The following results are obtained by simulation. The optimal extraction position of recycled flue gas (RFG) is gas preheater outlet, and the net power generation efficiency increases by 0.23% to 25.08%. As the preheating temperature increases from 230 to 400 °C, the net efficiency increases by 1.19% to 26.04%. The net efficiency increases first then decreases as the oxygen purity at ASU outlet increase from 89% to 97.4%, and the optimal value is the 94%. Finally, the optimal system is obtained when RFG is extracted from gas preheater outlet, the preheating temperature is 400 °C and the oxygen purity at ASU outlet is 94%. The net efficiency of the optimization system reaches 27.4%, increasing by 2.55%.